Advancing precision, safety, and education in D3 lymph node dissection for right hemicolectomy using mixed reality technology - Shunjin Ryu; Yuta Imaizumi; Shunsuke Nakashima; Keisuke Goto; Hyuga Kawakubo; Hironari Kawai; Takehiro Kobayashi; Ryusuke Ito; Yukio Nakabayashi (Scientific Reports)
Abstract Right hemicolectomy (RHC) is an important treatment for colorectal cancer. The superior mesenteric artery and superior mesenteric vein are known for their significant vascular variations. This study evaluated the short-term outcomes of integrating Mixed Reality (MR) technology into RHC for the treatment of colorectal cancer. Patients who underwent RHC for clinical stage II or III colon cancer between January 2015 and August 2024 were included. Patients were divided into two groups: the MR (+) group (n = 47), in which MR was used, and the MR (−) group (n = 145), in which MR was not used. MR using SYNAPSE VINCENT, Holoeyes MD, and HoloLens2 was utilized for detailed 3D visualization of the vascular anatomy preoperatively and intraoperatively. Forty-four patients per group were matched via propensity score matching and surgical outcomes were compared. In both groups, approximately 70% of the surgeries were performed by the training surgeon. Compared with the MR (−) group, intraoperative blood loss and hospital stay were decreased, and the number of lymph nodes harvested around the middle colic artery/vein were increased without prolonging the operative time in the MR (+) group. MR in RHC offers surgical precision, safety, enhanced patient recovery, and educational value.